The Effectiveness Of Application Of Cooperative Learning Model CRH (Course Review Horay) Assistant Video About Animation On Achievement and Learning Outcomes Of Physics - Jusriana, Andi (UIN Alauddin Makassar, 2022)
This study aims to 1) describe the description of the achievement and learning outcomes of physics students who are taught using the CRH (Course Review Horay) model assisted by video questions about animation to students of class XI MIA SMAN 6 Takalar. 2) Describing a description of the achievement and learning outcomes of students who are not taught physics by using the CRH (Course Review Horay) model with the aid of video animation questions for students in class XI MIA SMAN 6 Takalar. 3) Describe whether the CRH (Course Review Horay) model assisted by video about animation is effective on the achievement and learning outcomes of physics students in class XI MIA SMAN 6 Takalar. This type of research is a quasi-experimental research design with the non-equivalent post-test only control group design. This study took place at SMAN 6 Takalar with a population of 99 people from class XI MIA and the sample was 62 people from class XI MIA 1 and XI MIA 2. The results showed the average value of student learning achievement in the experimental class was 83.4 in the medium category, the average value of the learning outcomes test in the experimental class was 58.5 in the good and sufficient categories. While the average value of student learning achievement in the control class is 77.5 in the medium category, the average value of the control class learning achievement test is 42.42 in the sufficient category. The implication of this research is that the results of this study are expected to be used as comparisons and references in finding other learning models that can improve student achievement and learning outcomes, especially in physics subjects.